TELEMEDICINE IN PAEDIATRIC INFECTIOUS DISEASES - Singamayum Ashif (African Journal of Environmental Economics and Management, 2023)
Telemedicine is the remote practice of medicine through the use of information and communication technologies for the preven- tion, diagnosis, treatment and the management of various communicable and non-communicable diseases related to paediatrics. There is widespread use of telemedicine for the management of the acute and chronic infectious diseases. It is particularly found in those countries in which the majority of the population are living in the rural areas, far away from the third-level hospital center that are located in large urban areas. Obviously, telemedicine is being used in the developing countries. Telemedicine is increasingly representing the future and the beginning of the new era of healthcare system that will redefine the medical care for the treatment of infectious diseases, both acute and the chronic conditions in children.